Hydroponic Vegetable Product Advertisement Video Analysis and Development with MDLC Model - Jimmy Pratama; Andry Ramadhansyah (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2023)
Growing vegetables with a hydroponic system have the advantage of not requiring large areas of land and can produce good quality vegetable products continuously. The hydroponic system can be a solution for producing vegetables in areas that do not have large areas of land with soil conditions that make it impossible to grow vegetables conventionally, such as in the city of Batam. Hydroponic vegetables also have advantages over conventional vegetables such as longer shelf life, crunchier texture, and wider leaves. This research is expected to provide information to the public that hydroponic vegetables have advantages compared to conventional vegetables so that people's consumption of hydroponic vegetables increases. Media development was carried out using the MDLC method and media analysis was carried out using qualitative methods. The analysis was carried out by testing media experts and content experts using the Gregory formula with a validity coefficient of 1.00 and testing audience response using a Likert scale with a percentage of 93.25%.